Identifying Opportunities for Developing Nature-Based Sport Tourism to Improve Health in Papua: A Bibliometric Analysis of Research Over Ten Years - Guntoro, Tri Setyo; Prasetyo, Yudik; Putra, Miftah Fariz Prima; Nurhidayah, Dewi; Sinaga, Evi; Yuliana, Ela; Nanda, Fitri Agung (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to examine research trends around nature-based tourism, event-based sports tourism, and their relationship with government policies to identify potential opportunities for sustainable sports tourism development in Papua. Materials and methods. The methodological approach comprised using a bibliometric analysis by reviewing 997 scientific articles sourced from Scopus, PubMed, and Web of Science databases from 2014-2024. Harzing’s publish or Perish software was used to sort the articles, and VOSViewer software was used to analyze the articles. The review included the number of cluster groups, research themes related to sports tourism in the year groups, research trends around nature-based sports tourism, and gaps in sports tourism development. Results. There were eight cluster groups and five groups. The current research trends in the field of sports tourism comprise event-based sports tourism, nature tourism, the tourism industry, and social media. The research trends related to nature-based sports tourism include six keywords, namely nature-based tourism, nature connectedness, nature sport, nature-based events, nature-based recreation, and nature. Visitors, managers, communities, and governments benefit from the health and economic advantages of nature-based sports tourism. In developing nature-based sports tourism, it is essential to consider the sustainability of nature, cultural characteristics, and the form of activities offered. Local governments need to take part in efforts to develop and preserve nature-based sports tourism. Conclusions. The development of nature-based sports tourism with traditional sports activities has a great opportunity to be enhanced. This innovation certainly needs careful planning from determining goals, human resources, risk factors, and presenting an effective promotional strategies. The involvement of local government can facilitate the implementation of this planning.